Design and implementation of a low cost grid-connected 10 kw hydro power system - Lombard, Adriaan Cornelius Johannes (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2010.